Early Exercise Decision in American Options with Dividends, Stochastic Volatility, and Jumps - Cosma, Antonio; Galluccio, Stefano; Pederzoli, Paola; Scaillet, Olivier (Journal of Financial and Quantitative Analysis, 2020)
Using a fast numerical technique, we investigate a large database of investors’ suboptimal nonexercise of short-maturity American call options on dividend-paying stocks listed on the Dow Jones. The correct modeling of the discrete dividend is essential for a correct calculation of the early exercise boundary, as confirmed by theoretical insights. Pricing with stochastic volatility and jumps instead of the Black–Scholes–Merton benchmark cuts the amount lost by investors through suboptimal exercise by one-quarter. The remaining three-quarters are largely unexplained by transaction fees and may be interpreted as an opportunity cost for the investors to monitor optimal exercise.